Exploring Open-Source 3D Printing as a Transformative Design Tool: Empowering Designers and Enabling Innovation - McLaughlin, Katrina (FormAkademisk, 2023)
My practice explores how to transfer my design knowledge of embroidery and print into 3D printing technologies and software. My Doctoral practice-based research explores the rationale behind using open-source, low-cost 3D printing technologies and software, which enabled me to change, remix and use the 3D printer as a flexible design tool like a sewing machine. The research aims to investigate the digitalisation of traditional textile craft techniques to produce a new taxonomy of design applications. I have produced a collection of 3D-printed embellished textiles demonstrating my practice-based research's ongoing outcomes. By engaging with online communities and Open-Source Technologies, I have developed the skills to apply my specialist knowledge to this alternative technology to translate and interpret traditional textile and manipulation techniques. The exhibition will showcase these outcomes and demonstrate the opportunities within the fashion, textiles and costume industries. The post-production processes engage with my specialist background knowledge of print and dye techniques.